LITERATURE AS A TOOL FOR ENHANCING LANGUAGE SKILLS - Jumaniyazova Lobar Sirojiddin qizi (TADQIQOTLAR, 2025)
ABSTRACT This article explores the pivotal role of literature in enhancing language skills within English language learning contexts. Drawing upon empirical studies and theoretical frameworks, it examines how literature facilitates vocabulary acquisition, grammatical competence, cultural awareness, and critical thinking. The integration of literature into language education not only enriches linguistic proficiency but also fosters intercultural understanding and cognitive development. Various pedagogical strategies, such as literature circles and digital storytelling, are discussed to demonstrate the effectiveness of literature-based instruction. The article further addresses challenges related to text selection and learner variability, offering practical recommendations for educators.